2021
DOI: 10.3390/ijms22157799
|View full text |Cite
|
Sign up to set email alerts
|

Novel N-Substituted Amino Acid Hydrazone-Isatin Derivatives: Synthesis, Antioxidant Activity, and Anticancer Activity in 2D and 3D Models In Vitro

Abstract: A series of novel mono and bishydrazones each bearing a 2-oxindole moiety along with substituted phenylaminopropanamide, pyrrolidin-2-one, benzimidazole, diphenylmethane, or diphenylamine fragments were synthesized, and their anticancer activities were tested by MTT assay against human melanoma A375 and colon adenocarcinoma HT-29 cell lines. In general, the synthesized compounds were more cytotoxic against HT-29 than A375. 3-((4-Methoxyphenyl)(3-oxo-3-(2-(2-oxoindolin-3-ylidene)hydrazinyl)propyl)amino)-N’-(2-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 86 publications
0
30
0
Order By: Relevance
“…Naturally occurring indole, quinoline and indoloquinoline heterocyclic cores are particularly important due to their diverse biological activities, which inspire many researchers to synthesize series of hybrid systems with different spacers [ 8 , 9 , 10 , 11 ]. Natural and synthetic isatin scaffolds have received much attention from many researchers due to their wide pharmaceutical application as antimicrobial, antioxidant, anticancer and antimalarial agents [ 12 , 13 , 14 , 15 ]. On the other hand, quinoline’s core structure represents a promising surrogate in drug design and development.…”
Section: Introductionmentioning
confidence: 99%
“…Naturally occurring indole, quinoline and indoloquinoline heterocyclic cores are particularly important due to their diverse biological activities, which inspire many researchers to synthesize series of hybrid systems with different spacers [ 8 , 9 , 10 , 11 ]. Natural and synthetic isatin scaffolds have received much attention from many researchers due to their wide pharmaceutical application as antimicrobial, antioxidant, anticancer and antimalarial agents [ 12 , 13 , 14 , 15 ]. On the other hand, quinoline’s core structure represents a promising surrogate in drug design and development.…”
Section: Introductionmentioning
confidence: 99%
“…Compound effect on cell colony formation and growth was established by clonogenic assay, as previously published [ 45 ]. Briefly, MIA PaCa-2 and PANC-1 cells were seeded into 12-well plates (Corning) at a density of 200 cells/well in 1 mL of medium and treated with sunitinib derivatives at the concentrations representing 10% and 90% of calculated EC 50 value.…”
Section: Methodsmentioning
confidence: 99%
“…Further the important 20 amino acids have been connected to a number of substrates to achieve the potent biological activities like antibacterial (Kaminski and Feix, 2011), antifungal (Sakıyan et al, 2004), anticancer(Abd-Elhamid et al, 2021), inhibitors of Type B Monoamine Oxidase (Leonetti et al, 2007), antibrotic (Li et al, 2021). It was also observed that N-Substituted amino acids are more potent against a number of activities like PPARγ agonist activity (Peiretti et al, 2020), hyperalphalipoproteinaemic activity (Baggaley et al, 1988), anti-in ammatory activity (Sakıyan et al, 2004), anti-phlogistic activity(Abd-Elhamid et al, 2021), anti-hypertensive (Stanton et al, 1983), anti-oxidant activity (Tumosienė et al, 2021), and anti-phlogistic activity (Bruno et al, 1999).…”
Section: Introductionmentioning
confidence: 99%